Preparation method of size-adaptive bismuth-based nanoreactor with antibacterial effect as well as product and application of size-adaptive bismuth-based nanoreactor
By developing adaptively sized bismuth-based nanoreactors, using their dissociation characteristics in acidic environments and photothermal and nitric oxide release effects under near-infrared lasers, traditional photothermal therapy has been solved infiltration and temperature in biofilms. The lack of control has achieved efficient killing and precise treatment of bacterial biofilms.
Patent Information
- Application Number
- CN202411772470.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
AI Technical Summary
Existing photothermal bismuth preparations are difficult to penetrate and accumulate in the biofilm, and cannot completely remove the biofilm, and traditional photothermal therapy has difficulties in precise temperature control, increasing the risk of thermal damage to surrounding healthy tissues.
Adaptive size bismuth-based nanoreactors, including bismuth sulfide crosslinked nanoparticles, nitric oxide donors supported in bismuth sulfide crosslinked nanoparticles, and neutrophil membranes encapsulated in the outer layer of bismuth sulfide crosslinked nanoparticles . The nanoreactor can dissociate into ultra-small bismuth sulfide particles in the acidic environment of the bacterial biofilm, enhance its permeability, and release nitric oxide and produce photothermal effects under near-infrared irradiation to jointly kill bacteria.
It achieves accurate and efficient killing of bacterial biofilms, avoids thermal damage to surrounding healthy tissues, enhances antibacterial effects, and is especially suitable for antibacterial biofilms infection.
Smart Images

Figure CN119424363A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedicine technology and relates to a preparation method of a self-adaptive-size bismuth-based nanoreactor with antibacterial effect, a product and an application thereof. Background Art
[0002] Bacterial infection remains one of the major threats to human health. With the abuse and improper use of antibiotics, the problem of bacterial resistance has become increasingly serious, leading to the emergence of multidrug-resistant (MDR) strains, which greatly reduces the effectiveness of conventional antibiotic treatment. In addition, bacteria further increase their resistance by forming biofilms, which not only hinder the penetration of antimicrobial drugs, but also effectively protect bacteria from attacks by the host immune system. Faced with the current situation of declining antibiotic efficacy and increasing resistance, there is an urgent need to develop innovative antibacterial strategies and alternative treatments.
[0003] In order to meet this challenge, the application of nanomaterials in the field of antibacterial has attracted widespread attention in recent years. First of all, nanomaterials are new materials for bacteria, which can circumvent the resistance mechanisms that affect traditional antibiotics, and they can target bacterial biofilms. In addition, the antibacterial system of nanomaterials exhibits unique physical and chemical properties, including multiple antibacterial mechanisms such as photothermal therapy, photodynamic therapy, and metal ion release, and has become an emerging strategy to address multidrug-resistant bacterial infections. In addition, non-antibiotic treatments such as gas therapy also provide new directions for antibacterial treatment.
[0004] Photothermal therapy has attracted extensive attention due to its potential in treating biofilm-associated infections. It has spatial and temporal controllability, minimal invasiveness, moderate tissue penetration, and the ability to bypass bacterial resistance mechanisms. In particular, most photothermal materials can produce highly toxic reactive oxygen species under irradiation, which can kill pathogenic microorganisms by oxidatively damaging important biological molecules such as phospholipids, enzymes, proteins, and DNA of bacteria. Among them, bismuth-based nanomaterials have become promising photothermal agents in the field of antibacterial due to their excellent biocompatibility, high stability, semiconductor properties, strong near-infrared absorption ability, good photothermal conversion efficiency, and controllable morphology and size. In addition, in the medical field, bismuth agents are widely used to treat a variety of gastrointestinal diseases, such as gastritis and dyspepsia, due to their unique pharmacological effects. Therefore, the safety of bismuth agents in medicine has been widely recognized. However, traditional photothermal bismuth preparations cannot completely remove biofilms because they are difficult to fully penetrate and accumulate inside the biofilm, and in traditional photothermal therapy, the difficulty of precise temperature control increases the risk of thermal damage to surrounding healthy tissues.
[0005] Therefore, how to prepare a nano-bismuth agent, improve the photothermal resistance effect of nano-bismuth agents against drug-resistant bacterial infections, and solve the problems of antibiotic resistance, long-term toxicity and the limitations of existing antibacterial therapies have become urgent issues to be addressed. Summary of the invention
[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a method for preparing a bismuth-based nanoreactor with adaptive size and antibacterial effect, as well as a product and application thereof.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In the first aspect, the present invention provides a bismuth-based nanoreactor with adaptive size and antibacterial effect, wherein the bismuth-based nanoreactor comprises bismuth sulfide cross-linked nanoparticles, a nitric oxide donor loaded in the bismuth sulfide cross-linked nanoparticles, and a neutrophil membrane wrapped in the outer layer of the bismuth sulfide cross-linked nanoparticles (abbreviated as Bi2S3 / SNP@CM).
[0009] The bismuth-based nanoreactor involved in the present invention has an outer layer wrapped with a neutrophil membrane, has the ability to target inflammatory infection sites, and is pH responsive. In the acidic environment of the bacterial biofilm, the bismuth-based nanoreactor can dissociate into the size of the original ultra-small bismuth sulfide particles, allowing the ultra-small bismuth sulfide particles to exhibit "dynamic conformational change" in the body, preventing them from being quickly cleared by the kidneys during body fluid circulation. At the same time, the dissociated particles can more easily penetrate into the bacterial biofilm, thereby improving their effectiveness at the infection site.
[0010] The bismuth sulfide particles in the bismuth-based nanoreactor have a strong photothermal effect under near-infrared (NIR) irradiation, producing a local high-temperature sterilization effect. At the same time, under near-infrared (NIR) irradiation, the nitric oxide donor realizes the controllable release of NO, and NO and its generated byproducts such as peroxynitrite (ONOO - ) and nitrogen trioxide (N2O3) can effectively cause bacterial membrane lipid peroxidation and significantly damage the bacterial membrane structure. The release of NO can also promote wound healing, increase the production of myofibroblasts and collagen, and has a significant therapeutic effect.
[0011] The bismuth-based nanoreactor combines the photothermal effect with the NO antibacterial effect. The two effects work together to generate more free radicals, effectively triggering the oxidation of GSH in bacteria and destroying the antioxidant balance of bacteria. This mechanism not only aggravates the damage to bacterial DNA, but also enhances the killing ability of oxidation / nitrification stress on bacteria, thereby enhancing the antibacterial effect, which is especially suitable for antibacterial biofilm infection. The bismuth-based nanoreactor achieves precise and efficient antibacterial effects and is suitable for the treatment of refractory bacterial infections.
[0012] Preferably, the bismuth sulfide cross-linked nanoparticles are products obtained by sequentially subjecting bismuth sulfide particles to an amination reaction and a cross-linking reaction.
[0013] The product obtained by sequentially subjecting bismuth sulfide particles to amination reaction and cross-linking reaction is pH responsive. In the acidic environment of bacterial biofilm, bismuth-based nanoreactors can dissociate into the size of original ultra-small bismuth sulfide particles, allowing the ultra-small bismuth sulfide particles to exhibit "dynamic conformational change" in the body, preventing them from being quickly cleared by the kidneys during body fluid circulation. At the same time, the dissociated particles can more easily penetrate into bacterial biofilms, improving their effectiveness at the site of infection.
[0014] Preferably, the particle size of the bismuth sulfide particles is 1-10 nm, for example, 1 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.
[0015] Preferably, the particle size of the bismuth sulfide cross-linked nanoparticles is 100-150 nm, for example, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 150 nm, etc.
[0016] Preferably, the nitric oxide donor comprises sodium nitroprusside (abbreviated as SNP) and / or its hydrate.
[0017] In a second aspect, the present invention provides a method for preparing the bismuth-based nanoreactor according to the first aspect, the preparation method comprising the following steps:
[0018] (1) mixing bismuth sulfide cross-linked nanoparticles with a nitric oxide donor to obtain bismuth sulfide cross-linked nanoparticles loaded with a nitric oxide donor (abbreviated as Bi2S3 / SNP);
[0019] (2) Bismuth sulfide cross-linked nanoparticles loaded with nitric oxide donors are mixed with neutrophil membranes, and the product is extruded using a liposome extruder to obtain the bismuth-based nanoreactor (abbreviated as Bi2S3 / SNP@CM).
[0020] The preparation method of the bismuth-based nanoreactor involved in the present invention is green, efficient, low-cost, can realize macro-scale synthesis, and has good biocompatibility.
[0021] Preferably, the mixing treatment in step (1) is stirred in the dark at -10 to 10°C (e.g., -10°C, -8°C, -6°C, -4°C, -2°C, 0°C, 2°C, 4°C, 6°C, 8°C, 10°C, etc.) for 6 to 12 h (e.g., 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc.).
[0022] Preferably, the product is washed with deionized water after the mixing treatment in step (1).
[0023] Preferably, the mixing treatment in step (2) is ultrasonically treated at -10 to 10°C (e.g., -10°C, -8°C, -6°C, -4°C, -2°C, 0°C, 2°C, 4°C, 6°C, 8°C, 10°C, etc.) for 10-20min (e.g., 10min, 12min, 14min, 16min, 18min, 20min, etc.).
[0024] Preferably, the mass ratio of the neutrophil membrane to the bismuth sulfide cross-linked nanoparticles loaded with nitric oxide donor in step (2) is (0.2-2):1, for example, 0.2:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, etc.
[0025] Preferably, the extrusion in step (2) is performed 9-21 times, such as 9 times, 11 times, 13 times, 15 times, 17 times, 19 times, 21 times, etc. An odd number of times is more preferred.
[0026] Preferably, after the extrusion in step (2), the product is also subjected to membrane filtration treatment.
[0027] Preferably, after the extrusion in step (2), the product is also centrifuged at a centrifugal speed of 8000-12000 rpm, for example, 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, etc.; and a centrifugal time of 10-20 min, for example, 10 min, 13 min, 15 min, 18 min, 20 min, etc.
[0028] In the present invention, the method for preparing the bismuth sulfide cross-linked nanoparticles comprises the following steps:
[0029] (S1) mixing bismuth sulfide particles with an amination reagent to react to obtain amino-modified bismuth sulfide particles;
[0030] (S2) The amino-modified bismuth sulfide particles are mixed with a cross-linking agent to react to obtain bismuth sulfide cross-linked nanoparticles.
[0031] Preferably, the amination agent includes any one of polyethyleneimine, ethylenediamine, diethylenetriamine or triethylenetetramine, or a combination of at least two thereof.
[0032] Preferably, the mixing reaction in step (S1) is carried out under stirring conditions at 10-40°C (e.g., 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.) for 30-90 min (e.g., 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, etc.).
[0033] Preferably, after the mixed reaction in step (S1), the product is further subjected to dialysis purification treatment, and the dialysis bag has a molecular weight cutoff of 100-300 kDa, such as 100 kDa, 150 kDa, 200 kDa, 250 kDa, 300 kDa, etc.; the dialysis time is 24-48 h, such as 24 h, 30 h, 36 h, 40 h, 42 h, 48 h, etc.
[0034] Preferably, the cross-linking agent comprises terephthalaldehyde, glutaraldehyde or glyoxal.
[0035] Preferably, the mixed reaction in step (S2) is carried out under stirring conditions at 10-40°C (e.g., 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.) for 3-6h, e.g., 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, etc.
[0036] Preferably, after the mixing reaction in step (S2), the product is also centrifuged at a speed of 8000-12000 rpm, such as 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, etc.; and a centrifugation time of 10-20 min, such as 10 min, 13 min, 15 min, 18 min, 20 min, etc.
[0037] In the present invention, the method for preparing the bismuth sulfide particles comprises the following steps:
[0038] The aqueous dispersion of bismuth salt is mixed with sulfur-containing peptide and reacted in an alkaline environment to obtain the product.
[0039] Preferably, the molar ratio of the bismuth salt to the sulfur-containing peptide is (0.05-0.2):(0.5-1);
[0040] The specific point values in (0.05-0.2) can be selected from 0.05, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, etc.; the specific point values in (0.5-1) can be selected from 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.
[0041] Preferably, the sulfur-containing peptide comprises glutathione.
[0042] Preferably, the mixing is stirring at 35-45°C (e.g., 35°C, 37°C, 38°C, 40°C, 42°C, 43°C, 45°C, etc.) for 10-30 min (e.g., 10 min, 15 min, 20 min, 25 min, 30 min, etc.).
[0043] Preferably, the pH value of the alkaline environment is 9-11, for example, pH=9, pH=9.5, pH=10, pH=10.5, pH=11, etc.
[0044] Preferably, the reaction is carried out at 35-45°C (e.g., 35°C, 37°C, 38°C, 40°C, 42°C, 43°C, 45°C, etc.) for 18-24h (e.g., 18h, 19h, 20h, 22h, 23h, 24h, etc.).
[0045] Preferably, after the reaction is completed, the product is further dialyzed and purified, and the dialysis bag has a molecular weight cutoff of 1-3 kDa, such as 1000 Da, 1500 Da, 2000 Da, 2500 Da, 3000 Da, etc.; the dialysis time is 24-72 h, such as 24 h, 30 h, 36 h, 42 h, 48 h, 54 h, 60 h, 72 h, etc.
[0046] In a third aspect, the present invention provides use of the bismuth-based nanoreactor described in the first aspect in preparing a drug for improving or treating bacterial infectious diseases.
[0047] Preferably, the bacterial infectious disease comprises subcutaneous bacterial infection or diabetic skin wound infection.
[0048] Other specific point values within the above-mentioned numerical ranges may be selected. Considering the length and brevity of the article, the point values will not be listed here one by one.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The bismuth-based nanoreactor of the present invention is coated with a neutrophil membrane on its outer layer and has the ability to target inflammatory infection sites.
[0051] (2) The bismuth sulfide cross-linked nanoparticles in the bismuth-based nanoreactor involved in the present invention are pH responsive. In the acidic environment of the bacterial biofilm, the bismuth sulfide cross-linked nanoparticles can dissociate into the size of the original ultra-small bismuth sulfide particles, so that the ultra-small bismuth sulfide particles exhibit "dynamic conformational change" in the body, avoiding their rapid clearance by the kidneys during body fluid circulation. At the same time, the dissociated particles are easier to penetrate into the bacterial biofilm, thereby improving their effectiveness at the infection site.
[0052] (3) The bismuth sulfide particles in the bismuth-based nanoreactor involved in the present invention have a strong photothermal effect under near-infrared (NIR) irradiation, producing a local high-temperature sterilization effect.
[0053] (4) At the same time, under near-infrared (NIR) irradiation, the nitric oxide donor can realize the controlled release of NO, and NO and its generated byproducts such as peroxynitrite (ONOO -) and nitrogen trioxide (N2O3) can effectively cause bacterial membrane lipid peroxidation and significantly damage the bacterial membrane structure. The release of NO can also promote wound healing, increase the production of myofibroblasts and collagen, and has a significant therapeutic effect.
[0054] (5) The bismuth-based nanoreactor involved in the present invention combines the photothermal effect with the NO antibacterial effect. The two effects cooperate with each other to generate more free radicals, effectively triggering the oxidation of GSH in bacteria and destroying the antioxidant balance of bacteria. This mechanism not only aggravates the damage of bacterial DNA, but also enhances the killing ability of oxidation / nitrification stress on bacteria, thereby enhancing the antibacterial effect, which is particularly suitable for antibacterial biofilm infection. The bismuth-based nanoreactor achieves precise and efficient antibacterial effects and is suitable for the treatment of refractory bacterial infections. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 is a transmission electron microscope image of the ultra-small Bi2S3 particles prepared in Example 1;
[0056] Figure 2 is a transmission electron micrograph of the bismuth sulfide cross-linked nanoparticles prepared in Example 1;
[0057] Figure 3 is a transmission electron microscopy image of the bismuth-based nanoreactor (Bi2S3 / SNP@CM) prepared in Example 1;
[0058] Figure 4 is the X-ray photoelectron spectroscopy (XPS) image of ultrasmall Bi2S3 particles;
[0059] Figure 5 It is the UV-visible absorption spectra of ultrasmall Bi2S3 particles and bismuth sulfide cross-linked nanoparticles;
[0060] Figure 6 is a dynamic light scattering (DLS) graph of the products of steps (1) to (5) of Example 1;
[0061] Figure 7 1 is a graph showing the zeta potential measurement results of the products of steps (1) to (5) of Example 1;
[0062] Figure 8 This is the UV-visible absorption spectrum analysis diagram of ultra-small Bi2S3 particles;
[0063] Fig. 9 It is the heating curve of ultra-small Bi2S3 particles with different concentrations;
[0064] Fig.10 This is the result of the photothermal stability evaluation of ultra-small Bi2S3 particles;
[0065] Fig.11 It is the UV-visible absorption spectrum analysis diagram of free SNP molecules and SNP-loaded bismuth sulfide cross-linked nanoparticles (Bi2S3 / SNP);
[0066] Fig.12 is the NO release curve of Bi2S3 / SNP solution under near-infrared laser irradiation at different power levels under different pH conditions;
[0067] Fig.13 It is the NO release curve of PBS solution, SNP solution, Bi2S3 particle dispersion, and Bi2S3 / SNP solution under near-infrared laser irradiation at different concentrations;
[0068] Fig.14 It is a statistical diagram of the consumption of GSH by each group of samples under near-infrared laser irradiation or non-irradiation conditions;
[0069] Fig.15 It is the colony plate result diagram of the in vitro bactericidal effect of each group of samples on MRSA under near-infrared laser irradiation or non-irradiation conditions;
[0070] Fig.16 It is the colony statistics result diagram of the in vitro bactericidal effect of MRSA of each group of samples under near-infrared laser irradiation or non-irradiation conditions;
[0071] Fig.17 It is the colony plate result diagram of the in vitro bactericidal effect of MDRPA on each group of samples under near-infrared laser irradiation or non-irradiation conditions;
[0072] Fig.18 It is the colony statistics result diagram of the in vitro bactericidal effect of MDRPA on each group of samples under near-infrared laser irradiation or non-irradiation conditions;
[0073] Fig.19 It is the growth curve graph of each group of samples after treatment of MRSA;
[0074] Fig. 20 is the growth curve of each group of samples after MDRPA treatment;
[0075] Fig.21 It is a statistical graph of NO release after Bi2S3 / SNP, Bi2S3 particles or free SNP treated bacteria under NIR and dark conditions;
[0076] Fig. 22 It is a statistical graph of GSH consumption by Bi2S3 / SNP, Bi2S3 particles or free SNP after treating bacteria under NIR and dark conditions;
[0077] Fig.23It is a statistical graph of ROS production of bacteria after the bacteria were treated with Bi2S3 / SNP, Bi2S3 particles or free SNP under NIR and dark conditions;
[0078] Fig.24 This is the result diagram of the effect of NO produced by each group of samples on the migration of epithelial cells;
[0079] Fig.25 are scanning electron microscopy (SEM) observations of bacteria in MRSA and MDRPA biofilms after treatment with Bi2S3 / SNP, Bi2S3 particles, or free SNP;
[0080] Fig.26 are three-dimensional confocal laser scanning microscopy (CLSM) images of bacteria in MRSA and MDRPA biofilms after treatment with Bi2S3 / SNP, Bi2S3 particles, or free SNP;
[0081] Fig. 27 is the crystal violet staining result of bacteria in MRSA and MDRPA biofilms after treatment with Bi2S3 / SNP, Bi2S3 particles or free SNP;
[0082] Fig.28 is the infrared thermal imaging of subcutaneously infected mice treated with different samples during laser treatment;
[0083] Fig.29 This is the appearance of the infected area of subcutaneously infected mice after being treated with different samples;
[0084] Fig.30 This is a graph showing the growth of colonies on a plate of homogenate supernatant of tissues in the infected area of mice infected subcutaneously after being treated with different samples;
[0085] Fig.31 are the hematoxylin-eosin (H&E) staining, Masson's staining, and immunohistochemistry (IHC) staining images of subcutaneously infected mice after different sample treatments;
[0086] Fig.32 This is the infrared thermal imaging of diabetic skin wound infected mice after being treated with different samples during laser treatment;
[0087] Fig.33 This is a picture of the appearance of the infected area and the growth of colonies on the plate of tissue homogenate supernatant after different sample treatments in diabetic mice with skin wound infection;
[0088] Fig.34 are the hematoxylin-eosin (H&E), Masson's, and immunohistochemistry (IHC) staining images of diabetic skin wound-infected mice after different sample treatments;
[0089] Fig.35 This is the safety evaluation result diagram of each group of samples on HUVEC cells;
[0090] Fig.36 These are H&E staining images of the main organs (heart, liver, spleen, lung and kidney) of diabetic skin wound infected mice after being treated with different samples. DETAILED DESCRIPTION
[0091] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0092] Example 1
[0093] Preparation of bismuth-based nanoreactor (Bi2S3 / SNP@CM):
[0094] (1) Preparation of ultra-small Bi2S3 particles:
[0095] First, Bi(NO3)3·5H2O (0.1M, 1mL) was dispersed in water and stirred at 37°C for 5 minutes. Then, glutathione (0.25g, 1mL aqueous solution) was added to the above solution and continued to stir for 15 minutes. Then, 1M sodium hydroxide (NaOH) was added to adjust the pH to alkaline and react for 18 hours. At the end of the reaction, the color of the solution changed from yellow to black. The above solution was dialyzed for 1 day through a dialysis bag with a molecular weight cutoff (MWCO=3000Da).
[0096] (2) Amination modification of ultra-small Bi2S3 particles:
[0097] The ultra-small Bi2S3 solution was quickly added to a polyethyleneimine (PEI) solution (1 mL, 60 mg / mL) and reacted for 30 minutes. Subsequently, the mixture was dialyzed through a dialysis bag (Mw=100000) for 24 hours to obtain a Bi-PEI product.
[0098] (3) Preparation of bismuth sulfide cross-linked nanoparticles:
[0099] Terephthalaldehyde (21.5 g) was completely dissolved in 1 mL of anhydrous methanol, and 3 mL of Bi-PEI solution was added dropwise and stirred for 3 hours to complete the cross-linking reaction. After the reaction, the product was centrifuged at 9000 rpm for 20 minutes and washed twice to obtain bismuth sulfide cross-linked nanoparticles.
[0100] (4) Preparation of SNP-loaded bismuth sulfide cross-linked nanoparticles (abbreviated as Bi2S3 / SNP):
[0101] 4 mL of the prepared bismuth sulfide cross-linked nanoparticle solution was mixed with 500 mL of 1 mg / mL SNP and stirred in an ice bath in the dark for 6 hours. After the reaction was completed, the product was washed with deionized water.
[0102] (5) Preparation of bismuth-based nanoreactor (Bi2S3 / SNP@CM):
[0103] Neutrophil membranes were mixed with Bi2S3 / SNP at a mass ratio of 0.2:1 and sonicated at 4°C for 10 minutes. Subsequently, the mixture was extruded 11 times using a membrane extruder, and the product was sequentially passed through a 400 nm membrane and a 200 nm membrane, followed by centrifugation at 10,000 rpm for 10 minutes to obtain Bi2S3 / SNP@CM, which was stored in PBS at 4°C for later use.
[0104] Example 2
[0105] Characterization of the products of each step of Example 1:
[0106] (1) The morphology of the products of step (1), step (3) and step (5) of Example 1 was characterized by transmission electron microscopy. The results are as follows: Figure 1-Figure 3 As shown. Transmission electron microscopy (TEM) analysis results show that the average particle size of ultra-small Bi2S3 particles is 4.3±0.18nm. The ultra-small Bi2S3 nanoparticles were surface-modified with polyethyleneimine (PEI) and then cross-linked with terephthalaldehyde to form larger and irregularly shaped Bi2S3 structures, and this morphological change can be observed in the TEM images.
[0107] (2) X-ray photoelectron spectroscopy (XPS) was used to detect the ultra-small Bi2S3 particles in step (1) of Example 1. The results are as follows: Figure 4 As shown in the figure, the peaks at 158.1eV and 163.3eV correspond to Bi 3+ The two weaker peaks at 160.1eV and 163.5eV are attributed to the S2p3 / 2 and S2p1 / 2 orbitals.
[0108] (3) The ultra-small Bi2S3 particles of step (1) of Example 1 and the cross-linked product of step (3) were subjected to UV-visible absorption spectroscopy detection, as shown in FIG. Figure 5 As shown, the benzene ring absorption peak at about 300 nm confirms the successful cross-linking of ultrasmall Bi2S3 nanoparticles.
[0109] (4) Dynamic light scattering (DLS) and zeta potential measurements were performed on the products of steps (1) to (5) of Example 1. The results are as follows: Figure 6 and Figure 7As shown, the results indicate the successful preparation of products at each stage.
[0110] Example 3
[0111] Evaluation of photothermal performance:
[0112] In order to evaluate the photothermal effect of the ultrasmall Bi2S3 particles obtained in step (1) of Example 1, first, the ultraviolet-visible light absorption spectrum was analyzed. Figure 8 As shown, Bi2S3 particles exhibit strong absorption in the near-infrared region.
[0113] Then, aqueous solutions of different concentrations (0, 15, 30, 62.5, 125, and 300 μg / mL) were prepared and placed in 1.5 mL EP tubes. They were irradiated with near-infrared light of 808 nm for 540 seconds, and the temperature was recorded every 30 seconds using a digital near-infrared thermal imaging system (FLIR, Germany). Fig. 9 As shown, the temperature increased significantly with the increase of Bi2S3 aqueous solution concentration, indicating its high photothermal conversion efficiency and great potential as a NIR-mediated SNP nanoreactor.
[0114] Furthermore, the photothermal stability of the particles (62.5 μg / mL) was evaluated by five on / off cycles of 808 nm laser irradiation. Fig.10 As shown, after five heating / cooling cycles, the photothermal performance of the Bi2S3 particle dispersion remained consistent, further verifying its reliability as a stable photothermal agent.
[0115] Example 4
[0116] Evaluation of NO release performance and GSH consumption mechanism:
[0117] First, free SNP molecules and SNP-loaded bismuth sulfide cross-linked nanoparticles (abbreviated as Bi2S3 / SNP) were analyzed by UV-visible absorption spectroscopy. Fig.11 shown.
[0118] Then, 100 μL of Bi2S3 / SNP solution was placed in a 96-well plate at different pH conditions and heated at different power levels (0, 0.5, 1.0, 1.5 W / cm 2 ) at different time intervals. Then, the supernatant was collected and the concentration of NO was measured using a nitric oxide detection kit. The results are shown in Fig.12 As shown, compared with the Bi2S3 / SNP group at pH 7.4, the NO release of Bi2S3 / SNP at pH 6.0 continued to increase with the increase of power density.
[0119] Then, 100 μL of PBS solution, SNP solution, Bi2S3 particle dispersion, and Bi3S3 / SNP solution of different concentrations were placed in a 96-well plate and irradiated with a near-infrared laser (power of 1.5 W / cm 2 ), time is 8min), observe the change of NO release concentration with sample concentration, the results are as follows Fig.13 As shown, the high heat generated by Bi2S3 / SNP under laser irradiation plays a key role in triggering NO release and significantly improves the decomposition of SNP. The comprehensive experimental results show that the Bi2S3 / SNP nanoreactor can load SNP and achieve near-infrared activated spatiotemporal controllable NO release.
[0120] Then, the Ellman method was used to evaluate the changes in GSH concentration, specifically using 5,5′-dithiodinitrobenzoic acid (DTNB) to track the consumption of GSH. GSH solution (5mM) and samples from each experimental group were added to a 96-well plate, some samples were irradiated with 808nm light, and some samples were not irradiated with light (n=3). Subsequently, DTNB (100mM, 1μL) was added to each well. The hydrogen peroxide (H2O2) treatment group was used as a positive control. The absorbance at 412nm was measured by an enzyme reader to determine the GSH level. The results are shown in Figure 2. Fig.14 As shown, bismuth sulfide can induce in situ catalytic reactions under near-infrared irradiation, generate ROS with high cytotoxicity, and consume GSH. In addition, bismuth ions released by bismuth sulfide can further react with GSH in a weakly acidic environment, amplifying oxidative stress and exacerbating cell damage. Under NIR irradiation, the GSH loss rate of the Bi2S3 / SNP group was significantly higher than that of other control groups.
[0121] Example 5
[0122] Evaluation of in vitro antibacterial properties:
[0123] (1) Bacterial culture: MRSA and MDPRA were transferred into 5 mL LB medium using a sterile inoculation loop and cultured overnight in a shaking incubator at 37°C and 200 rpm. After overnight culture, the bacterial suspension was diluted to 1×10 7 CFU / mL for subsequent use.
[0124] (2) In vitro antibacterial test:
[0125] The antibacterial activity was evaluated by plate counting and OD600. 7CFU / mL of MRSA and MDRPA bacterial suspensions were treated as follows: 1) PBS control, 2) SNP, 3) Bi2S3, 4) Bi2S3 / SNP, 5) PBS+NIR, 6) SNP+NIR, 7) Bi2S3+NIR, 8) Bi2S3 / SNP+NIR.
[0126] According to the concentration of particles, the concentration of SNP, Bi2S3, and Bi2S3 / SNP in the experiment was 30 μg / mL, and the experiment was carried out at pH 6.0. The above mixed solutions were incubated at 37°C for 6 hours, and the laser irradiation parameters were set to 1.5 W / cm 2 , for 8 minutes. After 6 hours of treatment, the bacteria were resuspended in neutral LB medium for dilution. The diluted bacterial solution (100 μL) was spread on an agar plate and incubated at 37°C for another 12 hours. Finally, the bacterial colonies were analyzed and photographed. The colony morphology of the MRSA group is shown in the figure below. Fig.15 As shown in the colony statistics diagram Fig.16 The colony morphology of the MDRPA group is shown in Fig.17 As shown in the colony statistics diagram Fig.18 As shown. Under NIR irradiation, the treatment group had a significant antibacterial effect compared with the control group. When the Bi2S3 / SNP concentration increased from 10μg / mL to 30μg / mL, the antibacterial rate against MRSA and MDRPA reached 99%, and almost no antibacterial effect was observed under dark conditions. Fewer colonies were observed in the Bi2S3 / SNP group on the agar plate, indicating that the pH and NIR-responsive controlled release system promoted the release of NO within the biofilm, thereby enhancing the synergistic effect of photothermal therapy and NO gas therapy. This synergistic effect is essential for achieving efficient antibacterial and anti-biofilm activity.
[0127] To evaluate the long-term inhibitory effect, the growth curves of MRSA and MDRPA were determined by monitoring the optical density of the bacterial suspension at 600 nm using the same grouping method as above, respectively. Fig.19 and Fig. 20 The Bi2S3+NIR group significantly delayed bacterial growth in the first 12 hours, and the Bi2S3 / SNP group also showed a similar effect, which was attributed to the combined effect of NO and photothermal properties. It is worth noting that Bi2S3 / SNP completely inhibited bacterial growth, demonstrating its high antibacterial ability and long-lasting antibacterial effect.
[0128] Example 6
[0129] Discussion on antibacterial mechanism:
[0130] (1) The NO release behavior of bacteria treated with Bi2S3 / SNP, Bi2S3 particles or free SNP under NIR and dark conditions was evaluated. The specific operation process was as follows: MRSA was first mixed with different types of nanoreactors and incubated together for 4 hours. Subsequently, these mixtures were divided into two groups: one group was irradiated with near-infrared (NIR) for 8 minutes (power of 1.5 W / cm 2 ), and the other group was placed in a dark environment as a control. After the treatment, the bacteria were lysed by rapid freezing and thawing to collect the bacterial lysate. Finally, the NO detection kit was used to quantitatively detect the nitric oxide (NO) content in the collected bacterial lysate. By comparing the NO content under light and dark conditions, the effect of the nanoreactor on the NO produced by MRSA under the photothermal effect can be evaluated. The results are shown in Fig.21 As shown, the results showed that laser irradiation of SNP and Bi2S3 / SNP groups induced significant production of NO.
[0131] (2) Evaluate the ability of Bi2S3 / SNP, Bi2S3 particles and free SNP to deplete bacterial GSH. The specific operation process is as follows: First, after specific treatment of the bacteria, collect 500 μL of bacterial lysate. Next, mix these lysates with 5 μL of DTNB solution (concentration of 10 mg / mL) and incubate at 37°C for 60 minutes. This step allows DTNB to react with GSH to produce yellow 2-nitro-5-mercaptobenzoic acid (TNB), which has a maximum absorption peak at 412 nm. Finally, use a microplate reader to measure the absorbance of the reaction mixture at 412 nm to quantitatively analyze the GSH content. By comparing the absorbance values of different treatment groups, the effect of the treatment on the level of GSH in bacterial cells can be evaluated. Fig. 22 As shown, both Bi2S3 and Bi2S3 / SNP groups could deplete GSH under laser irradiation and non-irradiation conditions, and GSH depletion was significantly enhanced after irradiation.
[0132] (3) DCFH-DA was used to evaluate the ROS levels produced by bacteria treated with Bi2S3 / SNP, Bi2S3 particles, or free SNP under NIR irradiation / dark conditions. The specific operation process was as follows: First, MRSA was mixed with various nanoreactors and incubated together for 4 hours. After the treatment, the bacterial samples were collected and resuspended in an equal volume of phosphate buffered saline (PBS) for the next treatment. Then, the bacterial suspension was divided into two groups: one group was exposed to near-infrared (NIR) light for 8 minutes (power of 1.5 W / cm 2), and the other group was placed in a dark environment as a control. After light treatment, 10 μM DCFH-DA probe was added to the bacterial suspension, and the fluorescence intensity was measured at an excitation wavelength of 488 nm and an emission wavelength of 525 nm. DCFH-DA will be oxidized into DCF with enhanced fluorescence intensity after reacting with ROS. Therefore, by comparing the fluorescence intensity of different treatment groups, the effect of the nanoreactor on the ROS level in MRSA cells under the photothermal effect can be evaluated. Fig.23 As shown, the Bi2S3 / SNP+NIR group showed significantly higher ROS levels compared with other treatments.
[0133] (4) Evaluate the biological effects of NO. Nitric oxide (NO), as a gaseous signaling molecule, has a wide range of applications in the medical field, especially in immune regulation and wound healing. NO also has significant antibacterial properties. It effectively kills bacteria by inducing lipid peroxidation, cutting DNA, and interfering with protein function, and is not likely to cause bacterial resistance. Therefore, we tested the function of NO released in this system.
[0134] The specific implementation steps are as follows: HUVEC cells were seeded at a density of 5×10^5 cells / ml in a six-well culture plate and cultured to a density of 90%; a 200-μl pipette tip was used to draw a straight line in each well to form a gap where cells could not grow; the cells were treated with 50 μg / ml Bi2S3 / SNP, Bi2S3 particles or free SNP, and then exposed to near-infrared for 8 minutes; images were taken at 0h and 24h to monitor cell migration. The results are shown in Figure 2. Fig.24 As shown, the Bi2S3 / SNP treatment group promoted the healing of epithelial cells under NIR irradiation.
[0135] Example 7
[0136] Evaluation of antibacterial biofilm ability in vitro:
[0137] (1) Scanning electron microscopy (SEM) was used to observe the morphology of bacteria MRSA and MDRPA after treatment with Bi2S3 / SNP, Bi2S3 particles or free SNP. The treatment method was as follows: After different treatment steps, the bacterial sample was first centrifuged at 6000 rpm for 5 minutes, and then resuspended in 1 mL of 2.5% glutaraldehyde solution for fixation. The fixation process lasted for 12 hours, after which the sample was gradually dehydrated through ethanol solutions of increasing concentrations (10%, 30%, 50%, 70% and 90%, respectively), and immersed in each concentration of ethanol solution for 30 minutes. Finally, the bacterial sample was resuspended in 100 microliters of ethanol for SEM analysis. Fig.25As shown, compared with the other treatment groups, the MRSA biofilm showed more obvious damage after treatment with Bi2S3 / SNP laser irradiation group, and the bacteria in the biofilm died.
[0138] (2) The activity of the biofilm was determined by three-dimensional confocal laser scanning microscopy (CLSM) using the live / dead cell staining method. The treatment methods for each group were as follows: the treated biofilm was incubated with a mixed solution of SYTO 9 and PI for 30 minutes under light-proof conditions. After the incubation, the biofilm was gently rinsed with phosphate buffered saline (PBS) to remove excess dye, and then imaged and analyzed using CLSM. The final concentrations of Bi2S3 / SNP, Bi2S3, and SNP in the experiment were all 30 μg / mL. Fig.26 As shown, compared with the other treatment groups, the MRSA biofilm showed more obvious damage after treatment with the Bi2S3 / SNP laser irradiation group, and the bacteria in the biofilm were basically dead.
[0139] (3) Biofilms of MRSA and MDRPA were prepared in 24-well plates and exposed to different treatment conditions (PBS+NIR, SNP+NIR, Bi2S3+NIR, Bi2S3 / SNP+NIR) for 24 h. The final concentrations of Bi2S3 / SNP, Bi2S3, and SNP were all 30 μg / mL. The irradiation temperature was 1.5 W / cm 2 After treatment, the biofilm was washed three times with PBS, dried in an oven at 37°C for 1 hour, stained with 5% (volume ratio) crystal violet for 30 minutes, rinsed with PBS, and photographed after drying. Fig. 27 As shown, the Bi2S3 / SNP combined with laser irradiation treatment group significantly reduced the biomass of MRSA and MDRPA biofilms, which was significantly more effective than other treatments. Even without laser irradiation, the SNP and Bi2S3 groups also showed a certain ability to destroy biofilms. These results show that the Bi2S3 / SNP+NIR prepared by the present invention has a more efficient MRSA / MDRSA biofilm eradication efficiency.
[0140] Persistent bacterial infection is closely related to biofilm formation, which can lead to drug resistance and protect bacteria from the host immune system. Therefore, eradication of bacterial biofilm is more difficult than eliminating planktonic bacteria. From the above test results, it can be seen that the Bi2S3 / SNP+NIR prepared by the present invention has a high efficiency in eradicating bacterial biofilm.
[0141] Example 8
[0142] Improvement of subcutaneous infection symptoms:
[0143] (1) Construction of subcutaneous infection model: 100 μL of MRSA bacterial suspension (concentration of approximately 10^7 CFU / mL, suspended in PBS) was subcutaneously injected into the back area of shaved and disinfected anesthetized Balb / c mice for 24 hours to induce subcutaneous abscess formation.
[0144] (2) Grouping and intervention: The mice were randomly divided into six groups, with 5 mice in each group: PBS, SNP, Bi2S3, Bi2S3+NIR, Bi2S3 / SNP+NIR, and Bi2S3 / SNP@CM+NIR were treated respectively. The drug was administered by intravenous injection (dose of 300 μg / mL, depending on the particle dose), and then laser treatment (1.5 W / cm 2 , 8 minutes).
[0145] (3)Indicator observation:
[0146] During laser treatment, an infrared thermal imaging camera is used to capture thermal images of the infected area to monitor local temperature changes, such as Fig.28 As shown, Bi2S3 / SNP@CM can reach the bacterial infection site and accumulate at the infection site and induce high fever under NIR irradiation to help kill bacteria.
[0147] On the 1st, 3rd, 7th, 9th and 13th days after administration, the infected areas of mice in each group were observed and photographed. Fig.29 As shown, Bi2S3 / SNP@CM showed the best wound healing effect under laser irradiation compared with other treatment groups.
[0148] On the 14th day after administration, the skin tissue around the wound was collected, a portion of the tissue homogenate was diluted and the supernatant was spread on the culture medium plate, and the colony formation of each group was observed after culturing at 37°C for 24 hours. Fig.30 As shown, compared with the other treatment groups, almost no colony growth was observed in the Bi2S3 / SNP@CM laser irradiation group, indicating that the bacterial colonization at the infection site of mice in the Bi2S3 / SNP@CM laser irradiation group was significantly reduced, and MRSA-induced skin infection could be effectively cleared.
[0149] Another part of the tissue was fixed in 4% paraformaldehyde buffer. The fixed tissue was embedded in paraffin and sliced for hematoxylin-eosin (H&E) and Masson's staining to evaluate tissue healing and collagen deposition. Immunohistochemistry (IHC) staining was performed to detect the expression of CD31 and IL-6 to evaluate the level of neoangiogenesis and inflammation. Fig.31 As shown, compared with the other treatment groups, the mice in the Bi2S3 / SNP@CM group had less inflammatory cell infiltration in the infected tissues, higher collagen deposition, and better tissue healing.
[0150] Example 9
[0151] Improvement of diabetic skin wound infection symptoms:
[0152] (1) Construction of diabetic skin wound infection model:
[0153] After fasting for 12 hours, mice (model and age are the same as in Example 8) were intraperitoneally injected with 100 mg / kg of STZ once. The fasting blood glucose concentration of the mice was monitored to be ≥16.7 mmol / L, and the diabetic mice were considered to have been successfully modeled. The back skin of all the mice was shaved and disinfected, and then a nearly circular wound was cut on the back of the mice with sterile surgical forceps and scissors. 10 7 CFU of MRSA bacteria were placed in the wound of each mouse and the bacteria were allowed to grow for 48 hours. When the wound became red, swollen, or even festered, it proved that the mouse model of diabetic wound infection was successfully established.
[0154] (2) Grouping and intervention methods are the same as in Example 8.
[0155] (3)Indicator observation:
[0156] During laser treatment, an infrared thermal imaging camera is used to capture thermal images of the infected area to monitor local temperature changes, such as Fig.32 As shown, Bi2S3 / SNP@CM can reach the bacterial infection site and accumulate at the infection site and induce high fever under NIR irradiation to help kill bacteria.
[0157] On the 1st, 4th and 8th day of administration, the infected areas of mice in each group were observed and photographed. On the 8th day of administration, the skin tissue around the wound was collected, a portion of the tissue homogenate was diluted and the supernatant was spread on the culture medium plate. After culturing at 37°C for 24 hours, the colony formation of each group was observed. Fig.33 As shown, compared with the other treatment groups, the Bi2S3 / SNP@CM laser irradiation group had the best wound healing effect, and almost no colony growth was observed in the Bi2S3 / SNP@CM laser irradiation group, indicating that the Bi2S3 / SNP@CM laser irradiation group can effectively eliminate MRSA-induced skin infections.
[0158] Another part of the tissue was fixed in 4% paraformaldehyde buffer. The fixed tissue was embedded in paraffin and sliced for hematoxylin-eosin (H&E) and Masson's staining to evaluate tissue healing and collagen deposition. Immunohistochemistry (IHC) staining was performed to detect the expression of CD31 and IL-6 to evaluate the level of neoangiogenesis and inflammation. Fig.34 As shown, compared with the other treatment groups, the mice in the Bi2S3 / SNP@CM group had less inflammatory cell infiltration in the infected tissues, higher collagen deposition, and better tissue healing.
[0159] Example 10
[0160] Biosafety Assessment:
[0161] (1) Cytotoxicity test:
[0162] HUVEC cells were cultured in DMEM medium containing 10% FBS and 1% penicillin-streptomycin, seeded in 96-well plates, and exposed to different doses of Bi2S3 / SNP@CM for 24 h. Cell viability was then assessed using the CCK-8 method, and the absorbance was measured at 450 nm using a microplate reader. The results are shown in Figure 2. Fig.35 As shown in the figure, no cytotoxicity was detected when the concentration of Bi2S3 / SNP@CM was lower than 200 μg / mL. This indicates that the Bi2S3 / SNP@CM nanoreactor has good biocompatibility and is expected to become a candidate material for treating wound infection.
[0163] (2) After the experiment in Example 9, mice in each group were killed and their main organs (heart, liver, spleen, lung and kidney) were collected for H&E staining. Tissue sections were observed under a microscope to evaluate the in vivo biosafety. Fig.36 As shown, no obvious pathological reactions were observed in various organs. In summary, these experimental results show that Bi2S3 / SNP@CM has good biosafety within a certain concentration range.
[0164] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0165] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0166] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A self-adaptive-sized bismuth-based nanoreactor with antibacterial effect, characterized in that: The bismuth-based nanoreactor comprises bismuth sulfide cross-linked nanoparticles, nitric oxide donors loaded in the bismuth sulfide cross-linked nanoparticles, and neutrophil membranes wrapped in the outer layer of the bismuth sulfide cross-linked nanoparticles.
2. The bismuth-based nanoreactor according to claim 1, characterized in that: The bismuth sulfide cross-linked nanoparticles are products obtained by sequentially subjecting bismuth sulfide particles to an amination reaction and a cross-linking reaction; Preferably, the particle size of the bismuth sulfide particles is 1-10 nm; Preferably, the particle size of the bismuth sulfide cross-linked nanoparticles is 100-150 nm; Preferably, the nitric oxide donor comprises sodium nitroprusside and / or its hydrate.
3. The method for preparing a bismuth-based nanoreactor according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing bismuth sulfide cross-linked nanoparticles with a nitric oxide donor to obtain bismuth sulfide cross-linked nanoparticles loaded with the nitric oxide donor; (2) Bismuth sulfide cross-linked nanoparticles loaded with nitric oxide donors are mixed with neutrophil membranes, and the product is extruded using a liposome extruder to obtain the bismuth-based nanoreactor.
4. The method for preparing a bismuth-based nanoreactor according to claim 3, characterized in that: The mixing treatment in step (1) is stirred at -10 to 10° C. in the dark for 6 to 12 hours; Preferably, the product is washed with deionized water after the mixing treatment in step (1).
5. The method for preparing a bismuth-based nanoreactor according to claim 3 or 4, characterized in that: The mixing treatment in step (2) is ultrasonically treated at -10 to 10° C. for 10 to 20 minutes; Preferably, the mass ratio of the neutrophil membrane to the bismuth sulfide cross-linked nanoparticles loaded with nitric oxide donor in step (2) is (0.2-2):1; Preferably, the extrusion in step (2) is performed 9 to 21 times; Preferably, after the extrusion in step (2), the product is further subjected to membrane filtration treatment; Preferably, after the extrusion in step (2), the product is centrifuged at a speed of 8000-12000 rpm for a time of 10-20 min.
6. The method for preparing a bismuth-based nanoreactor according to any one of claims 3 to 5, characterized in that: The method for preparing the bismuth sulfide cross-linked nanoparticles comprises the following steps: (S1) mixing bismuth sulfide particles with an amination reagent to react to obtain amino-modified bismuth sulfide particles; (S2) The amino-modified bismuth sulfide particles are mixed with a cross-linking agent to react to obtain bismuth sulfide cross-linked nanoparticles.
7. The method for preparing a bismuth-based nanoreactor according to claim 6, characterized in that: The amination agent includes any one of polyethyleneimine, ethylenediamine, diethylenetriamine or triethylenetetramine, or a combination of at least two thereof; Preferably, the mixing reaction in step (S1) is carried out at 10-40° C. with stirring for 30-90 min; Preferably, after the mixed reaction in step (S1), the product is further subjected to a dialysis purification treatment, the molecular weight cut-off of the dialysis bag is 100-300 kDa, and the dialysis time is 24-48 h; Preferably, the cross-linking agent comprises terephthalaldehyde, glutaraldehyde or glyoxal; Preferably, the mixed reaction in step (S2) is carried out under stirring at 10-40° C. for 3-6 hours; Preferably, after the mixing reaction in step (S2), the product is centrifuged at a speed of 8000-12000 rpm for a time of 10-20 min.
8. The method for preparing a bismuth-based nanoreactor according to claim 6, characterized in that: The preparation method of the bismuth sulfide particles comprises the following steps: The aqueous dispersion of the bismuth salt is mixed with the sulfur-containing peptide and reacted in an alkaline environment to obtain; Preferably, the molar ratio of the bismuth salt to the sulfur-containing peptide is (0.05-0.2):(0.5-1); Preferably, the sulfur-containing peptide comprises glutathione; Preferably, the mixing is stirring at 35-45° C. for 10-30 min; Preferably, the pH value of the alkaline environment is 9-11; Preferably, the reaction is carried out at 35-45°C for 18-24h; Preferably, after the reaction is completed, the product is further subjected to a dialysis purification treatment, the molecular weight cutoff of the dialysis bag is 1-3 kDa, and the dialysis time is 24-72 h.
9. Use of the bismuth-based nanoreactor according to claim 1 or 2 in preparing a drug for improving or treating bacterial infectious diseases.
10. The use according to claim 9, characterized in that: The bacterial infectious diseases include subcutaneous bacterial infection or diabetic skin wound infection.
Citation Information
Patent Citations
Nucleic acid molecule-loaded acid response polymer modified bismuth elementary substance nanosheet as well as preparation method and application thereof
CN112315975A
Near-infrared response antibacterial nano composite hydrogel dressing
CN115317660A
Nano antibacterial photo-thermal material as well as preparation method and application thereof
CN115444942A
Fluorescent sulfur quantum dot as well as synthesis method and application thereof
CN115960603A
Nano composite material Fe / TNT-NM and preparation method and application thereof
CN117860704A